2000
DOI: 10.1002/1529-0131(200002)43:2<400::aid-anr21>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Association of mild acetabular dysplasia with an increased risk of incident hip osteoarthritis in elderly white women: The study of osteoporotic fractures

Abstract: Acetabular dysplasia, defined by a decrease in the center-edge angle, is associated with a modestly increased risk of incident hip OA in elderly white women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
87
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 157 publications
(91 citation statements)
references
References 12 publications
2
87
0
2
Order By: Relevance
“…A variety of radiographic parameters have been used as surrogates for predicting acetabular load concentration, but the relationship between these parameters and OA causation remains unclear. Numerous studies have reported correlation between the CE angle and OA (Chung et al, 2010;Jacobsen and Sonne-Holm, 2005;Lane et al, 2000;Murphy et al, 1995;Reijman et al, 2005), while others have concluded there is no relationship (Johnsen et al, 2009;Lau et al, 1995). It is not possible currently to predict degenerative progression to OA based upon commonly accepted definitions of radiographic parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of radiographic parameters have been used as surrogates for predicting acetabular load concentration, but the relationship between these parameters and OA causation remains unclear. Numerous studies have reported correlation between the CE angle and OA (Chung et al, 2010;Jacobsen and Sonne-Holm, 2005;Lane et al, 2000;Murphy et al, 1995;Reijman et al, 2005), while others have concluded there is no relationship (Johnsen et al, 2009;Lau et al, 1995). It is not possible currently to predict degenerative progression to OA based upon commonly accepted definitions of radiographic parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Developmental dysplasia of the hip (DDH) is an important disease leading to osteoarthritis (OA) (Hasegawa et al, 1992;Jacobsen and Sonne-Holm, 2005;Lane et al, 2000), and it is well established that high stress concentrations during weight-bearing ambulation cause OA (Mavcic et al, 2008;Pompe et al, 2007). Historically, static geometric factors on radiography, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Forty percent to 50 % of patients with residual hip dysplasia without subluxation suffer of advanced osteoarthritis at the age of 50 [5][6][7]. In cases with instability and subluxation of the hip, end stage osteoarthritis develops in nearly 100 % of all cases [2,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, [17,20,23] hip dysplasia and OA have typically been analyzed as binary variables. However, the definitions of the two clinical entities have differed considerably among different authors.…”
Section: Discussionmentioning
confidence: 99%
“…However, the definitions of the two clinical entities have differed considerably among different authors. In two epidemiologic studies, the cutoff points for CE angle in assessment of hip dysplasia ranged from 20°to 30° [17,20]; and the definition of hip OA in epidemiologic studies was based on self-reported assessment, clinically measured range of motion, radiographic scales, joint width measurements, or the risk of progression to THA. However, the choice of the particular outcome end point of hip OA substantially alters the results and conclusions [17,23,32].…”
Section: Discussionmentioning
confidence: 99%